On the growth of the thermally modified non-resonant streaming instability. Issue 2 (10th November 2020) - Marret, A; Ciardi, A; Smets, R; Fuchs, J
ABSTRACT: The cosmic rays non-resonant streaming instability is believed to be the source of substantial magnetic field amplification. In this work, we investigate the effects of the ambient plasma temperature on the instability and derive analytical expressions of its growth rate in the hot, demagnetized regime of interaction. To study its non-linear evolution, we perform hybrid-PIC simulations for a wide range of temperatures. We find that in the cold limit, about two-thirds of the cosmic rays drift kinetic energy is converted into magnetic energy. Increasing the temperature of the ambient plasma can substantially reduce the growth rate and the magnitude of the saturated magnetic field.